TINDAKAN PEMERINTAH KOTA DUMAI SEBAGAI UPAYA MENCEGAH BANJIR PASANG KELING (ROB) TAHUN 2023-2024 - Utami, Annisa Hegyana; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study examines the actions of the Dumai City Government in preventing tidal flooding (rob) during the period 2023–2024. Tidal flooding is a recurring phenomenon in the coastal areas of Dumai City and has significant impacts on the socio-economic conditions of the community. This research employs a qualitative approach with a descriptive method. The research locations include the Dumai City Public Works Office, the Dumai City Regional Disaster Management Agency (BPBD), as well as several tidal flood-affected urban villages, namely Rimba Sekampung, Simpang Tetap Darul Ihsan, and Ratusima. Primary data were collected through interviews with government officials and affected communities, while secondary data were obtained through documentation studies, including laws and regulations, flood management reports, tidal flood potential maps, and documentation of flood management activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The analysis is based on the theory of governmental legal actions proposed by Prof. Aminuddin Ilmar, which classifies legal actions into public legal actions and private legal actions. The results indicate that the Dumai City Government has implemented various public legal actions, including the formulation of regional regulations, issuance of decisions and policies related to flood management, and the implementation of the Khidmat Flood Management Program through the development of flood control infrastructure such as embankments, floodgates, and drainage systems, as well as private legal actions through cooperation agreements with third parties in carrying out technical activities in the field. Based on the findings, these governmental actions demonstrate the application of principles of governmental law in managing coastal disasters aimed at protecting the community from the impacts of tidal flooding. Keywords : Dumai City Government, Legal Actions, Tidal Flood (Rob)